PENGARUH PROGRAM PARENTING TERHADAP KEMANDIRIAN ANAK DI PAUD CAHAYA BUNDA DESA SUMBER AGUNG KECAMATAN MARGO TABIR KABUPATEN MERANGIN TAHUN PELAJARAN 2023/2024 - Uying Hapid Alatas; Aksul Dewi Fikra; Henky Setiadi; Susilawati Susilawati; Rizal Fadli (CV. Denasya Smart Publisher, 2026)
This research is motivated by the lack of parental enthusiasm in participating in the parenting program at Cahaya Bunda Early Childhood Education (PAUD) in Sumber Agung Village, resulting in low attendance and limited understanding of the program's purpose. Additionally, low levels of children's independence were observed, often characterized by crying and shyness during parenting sessions. This study aims to determine the effect of the parenting program on children's independence at Cahaya Bunda PAUD in Sumber Agung Village. This research uses a quantitative correlational method. The data collection instrument was a validated questionnaire. The subjects consisted of 52 children and 52 parents, selected using purposive sampling. Data analysis was performed using simple linear regression, coefficient of determination, and t-test with SPSS Statistics 26. The results showed that the success rate of the parenting program was 42.30% (score range 36–44), while children's independence was 30.76% (score range 23–31). The normality test result was sig. 0.200, and the linearity test was sig. 0.099, indicating that the data met the analysis requirements. Hypothesis testing showed r count < r table (0.075 < 0.279) and t count < t table (0.596 < 1.684), leading to the acceptance of H₀. It is concluded that the parenting program does not have a significant effect on children's independence at Cahaya Bunda PAUD in Sumber Agung Village.